2005
DOI: 10.2754/avb200574010009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dopamine on Rat Uterine Motility in vitro

Abstract: Czerski A., W. Zawadzki, M. Zawadzki, Z. Czerska: Influence of Dopamine on Rat Uterine Motility in vitro. Acta Vet. Brno 2005, 74: 9-15.The effect of dopamine on spontaneous rhythmic contractions of isolated rat uterine muscles was examined. The experiments were carried out on 25 female Buffalo rats aged between 4-6 months. Myometrial tissue (1.5-2 cm long) was set up in 4 isolated organ baths (20 ml) at 37 °C. After recording the pattern of myometrial tissue spontaneous motility: dopamine, domperidone, metocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The epithelial cells of the nipple are electrically connected to each other. There is a free flow of small molecules such as nucleotides and ions (Shen et al 1976;Czerski et al 2005). The flow is possible thanks to the presence of ion-metabolic connection between the cells (gap junction), which were confirmed by electron microscopy (Pitelka et al 1973;Peracchia and Dulhunky 1976).…”
Section: Discussionmentioning
confidence: 87%
“…The epithelial cells of the nipple are electrically connected to each other. There is a free flow of small molecules such as nucleotides and ions (Shen et al 1976;Czerski et al 2005). The flow is possible thanks to the presence of ion-metabolic connection between the cells (gap junction), which were confirmed by electron microscopy (Pitelka et al 1973;Peracchia and Dulhunky 1976).…”
Section: Discussionmentioning
confidence: 87%
“…Propranolol increases uterine contractions in pregnant women [14].Some studies have shown that uterine myometrium beta-adrenergic receptors in pregnant women are more than in non-pregnant women;therefore, compounds that can block adrenergic can increase uterine contractions.β2-adrenergic receptor may also be reduced at the time of delivery and reducing function the of these receptors cause uterine contraction during childbirth.Propranolol blocks these receptors and increases the strength of uterine contractions and reduces the duration of active phase and second stage of labor [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…These findings need another investigation, because MAO-B and MAO-A are responsible for the DA degradation and DA was also detected in the human [20] and cow [21] oviduct compartments. Moreover, the addition of DA into the incubation bath significantly reduced the strength and frequency of spontaneous rhythmic contractions of the rat uterus [23]. NA was also identified in bovine oviductal fluid [24], and it could influence the oviduct epithelium via adrenergic receptors, which have been shown in the oviduct epithelian cells of several species [25,26].…”
Section: Discussionmentioning
confidence: 91%